Bird Dispersal as a Pre-Adaptation for Domestication in Legumes: Insights for Neo-Domestication - Brǿnnvik, Hester; von Wettberg, Eric J. (Frontiers in Plant Science, 2019)
The first chapter of Darwin’s On the Origin of Species famously used examples of human selection of domesticated plants and animals to lay the groundwork for the Theory of Evolution (Darwin 1859). Since at least the works of Darwin (1868), domestication of plants and animals have been used as major examples of strong selection radically altering the morphology, architecture, and behavior of organisms on which our contemporary society relies for food, fiber and fuel. Consequently, it is not surprising that crop domestication remains a vibrant area of research. Despite this ongoing interest in the field of domestication, we greatly lack ecological and natural history studies of crop wild relatives in their wild settings.